TINJAUAN YURIDIS PENYELESAIAN TINDAK PIDANA KEKERASAN FISIK TERHADAP ANAK DIDIK YANG DILAKUKAN OLEH GURU MENURUT HUKUM PIDANA INDONESIA - Arga Chon Feriandref; Tri Widiastuti, Mubaraq, Othman Ballan, Eka Ermala, Duwi Aryadi (JOURNAL OF LAW AND NATION, 2024)
Based on Article 2 point 1 of Law Number 14 of 2005 that teachers have a position as professional staff at the levels of basic education, secondary education, and early childhood education in the formal education pathway appointed in accordance with statutory regulations. However, in providing education to students, teachers often take actions that are punishing and not educative, either in the form of physical actions that can cause danger to students' conditions or words that are harsh and inappropriate to say. These acts in the criminal law and the Child Protection Act can be categorized as crimes in the education sector. so the authors are interested in conducting research outlined in the form of a thesis in the form of analyzing the settlement of criminal acts of physical violence committed by teachers against students, where this act is a violation of human rights with the aim of knowing the factors causing criminal acts of physical violence against students committed by teachers; analyze the settlement of criminal acts of physical violence against students committed by teachers according to Indonesian criminal law; and analyzing the role of the government and related parties in resolving criminal acts of physical violence committed by teachers against students. The results showed that the factors causing the criminal act of physical violence against students committed by the teacher were influenced by the teacher himself, students, family and the environment, causing a bad perception of the students; Settlement of criminal acts of physical violence against students committed by teachers according to Indonesian criminal law through the criminal justice system that violates statutory regulations, namely the Criminal Code, Law Number 35 of 2014 concerning Child Protection and the role of the government and related parties in resolving criminal acts  of physical violence that carried out by teachers to students so that child-friendly schools are formed by implementing technical guidelines for the Guide to Preventing Violence against Children in Families, Communities and Educational Institutions that involve the participation of the community, families and educational institutions in cooperation and coordination in the form of facilitation, outreach and advocacy on prevention violence against children in educational institutions. The suggestions from the results of this study are to increase the role of government, local government, society, families, teachers and parents or guardians who are obliged and responsible for the implementation of child protection from violence in educational institutions and increase the simultaneous socialization of the implementation of Law Number 35 of 2014. Providing legal protection for students in educational institutions so that the welfare of the children is achieved during their education.